Religiosity in Rice Harvesting Ritual (A Case Study on Dayak’s Religious Phenomena in West Borneo) - Herlina, Herlina; Andayani, Andayani; Waluyo, Herman J.; Setiawan, Budhi (Opción, 2019)
Dayak in West Borneo already have a certain religion to guide their way of life. However, in rice harvesting ritual, animism and dynamism can be obviously seen. The aim of this research is to know the reason of doing rice harvesting ritual. Used descriptive qualitative method in the form of case study. Fundamental reasons that underlie rice harvesting ritual that is the Dayak are to preserve the culture and respect the ancestors, they think that culture exists before religion does. They believe that either culture and religion refer to God though there are differences on the ways used in the ritual.